2018
DOI: 10.1016/j.vacuum.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Ln 2 NiO 4+δ (Ln = La, Pr, Nd) coatings deposited by reactive magnetron sputtering as cathode material for intermediate temperature solid oxide fuel cell

Abstract: ARTICLE INFO ABSTRACT Keywords:Rar-arth nickelates Reactive magnetron sputtering lntermediate-temperature solid oxide fuel cell (IT-SOFC)This work focuses on the comparison of ln Ni O coatings (ln= La, Nd, Pr) deposited by reactive rnagnetron sputtering using Plasma Emission Monitoring (PEM) which allows high deposition rate. Each layer is deposited by different steps. The optimal regulation setpoint for oxide rare earth deposition is determined and then the current dissipated on the nickel target is adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…La 2 NiO 4 is a typical K 2 NiF 4 -type material that exhibits excellent performance on surface oxygen exchange and chemical stability from room temperature up to 1300 • C [10,11]. In addition, the thermal expansion coefficient of La 2 NiO 4 (13.0 × 10 −6 K −1 ) is close to that of the commonly used electrolyte yttria stabilized zirconia (YSZ, 11.6 × 10 −6 K −1 ) and ferritic steel interconnect materials (11.0-12.5 × 10 −6 K −1 ) [12,13]. The application of La 2 NiO 4 to half cells and single cells with different electrolytes has been studied and has shown interesting results.…”
Section: Introductionmentioning
confidence: 60%
“…La 2 NiO 4 is a typical K 2 NiF 4 -type material that exhibits excellent performance on surface oxygen exchange and chemical stability from room temperature up to 1300 • C [10,11]. In addition, the thermal expansion coefficient of La 2 NiO 4 (13.0 × 10 −6 K −1 ) is close to that of the commonly used electrolyte yttria stabilized zirconia (YSZ, 11.6 × 10 −6 K −1 ) and ferritic steel interconnect materials (11.0-12.5 × 10 −6 K −1 ) [12,13]. The application of La 2 NiO 4 to half cells and single cells with different electrolytes has been studied and has shown interesting results.…”
Section: Introductionmentioning
confidence: 60%
“…Then, the information is transferred to a computer where a program developed under Labview® monitors the oxygen flow rate to maintain the selected intensity of the optical signal of the zirconium line. For more details concerning the plasma emission monitoring techniques you can see our previous work on the elaboration of the electrolyte (12)(13) and cathode material for SOFC (14).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Januschewsky et al found that La 0.8 Sr 0.2 CoO 3−δ thin films prepared by PLD improved the performance as the deposition temperature decreased, suggesting that the surface of the amorphous cathode could be highly active for oxygen incorporation. Magnetron sputtering was also successfully used for deposition of thin film cathodes, such as Ln 2 NiO 4 (Ln = La, Pr, Nd), or nanoscaled interlayers based on La 0.6 Sr 0.4 CoO 3−δ and La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ , resulting in improved fuel-cell performance. In this regard, graded electrodes, which include more than a single layer, have attracted much interest recently due to the possibility of combining several functionalities, which may improve the electrochemical performance .…”
Section: Introductionmentioning
confidence: 99%